PENGARUH KONSUMSI PANGAN FUNGSIONAL TERHADAP STATUS GIZI IBU HAMIL DI KELURAHAN PADANG MERBAU KECAMATAN PADANG HULU KOTA TEBING TINGGI - riska maulidanita (Fakultas Ilmu Kesehatan, 2025)
The health of pregnant women is greatly influenced by adequate nutritional status during pregnancy. One of the efforts to improve the nutritional status of pregnant women is through the consumption of functional foods that contain nutrients and bioactive components that are beneficial to health. This study aims to determine the effect of functional food consumption on the nutritional status of pregnant women in Padang Merbau Village, Padang Hulu District, Tebing Tinggi City. This study uses a quantitative method with a cross sectional analytical design. The population in this study is all pregnant women in the region with a sample of 25 respondents, which were taken using the total sampling technique. Data on functional food consumption was collected through questionnaires, while the nutritional status of pregnant women was measured using anthropometric indicators. Data analysis was carried out univariate and bivariate using the Chi-Square test. The results showed that most of the respondents had adequate functional food consumption, namely 15 people (60%), and the nutritional status of pregnant women was mostly in the adequate category, namely 13 people (52%). The results of the Chi-Square test showed a p-value of < 0.05 which indicates that there is an influence of functional food consumption on the nutritional status of pregnant women. The conclusion of this study is that functional food consumption has a significant effect on the nutritional status of pregnant women. Therefore, efforts are needed to improve nutrition education related to the use of functional foods to support the health of pregnant women and fetuses.